EKONOMI POLITIK MEDIA DI INDONESIA - Halida Bahri; Masriadi (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2018)
Media company becomes a unique company in the industrial sector of Indonesia. On the one hand, media has to keep its independence in running the activities. On another hand, media is an industry, thus it certainly runs for profits. Keeping the independence in a media industry requires a skillful management. In this context, studying the politic economy of the media becomes necessary. The business of the media starts from selling the prints, advertisements, and is getting more developed these days. This paper studies the transformation of mass media in Indonesia from the perspective of politic economy.